Faktor yang Berhubungan dengan Berat Bayi Lahir Rendah - Mirawati Mirawati; Pratiwi Puji Lestari; Rr. Sri Nuriaty Masdiputri; Mahfuzhah Deswita Puteri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Babies with low birth weight are 20 times more at risk of dying than babies who weigh more. The incidence of low birth weight is still high. From the many studies that have been conducted, it is known that nutritional status is one of the factors that can affect birth weight. This study aims to analyze the factors associated with infant birth weight. The research method used a cross-sectional design by linking the variables of age, parity, gestational age and complications with the incidence of low birth weight. Samples were taken using the Consecutive sampling technique. The number of samples obtained was 96 people. Data analysis was performed using the chi square test. The results of the study found that there was a relationship between maternal age and the incidence of low birth weight, p value 0.04 <α (0.05) and age at risk 1,718 times more vulnerable to giving birth to low birth weight babies while the variables parity, gestational age and Complications are not related to Low Birth Weight.